Interaction analysis between creative self-efficacy and entrepreneurial profile in predicting entrepreneurial intention among university students (Management and Connections Journal, 2021)
Entrepreneurial intention predicts a new business creation. The development of entrepreneurial characteristics occurs throughout life, but at higher education, actions are more frequent and effective. In that context, we aimed to verify the interaction between entrepreneurial profile (PE) and creative self-efficacy (AE) in the prediction of entrepreneurial intention (IE) among university students. We sampled 309 students from Law (n = 30), Economics (n = 39), Mechatronics Engineering (n = 43), Mechanical Engineering (n = 43), Pedagogy (n = 42), Psychology (n = 67), International Relations (n = 35).  We applied scales with evidence of empirical validity for all constructs. We found that the direct impacts of PE on IE; also it showed positive and negative interactions of PE * AE on IE, which demonstrates that PE needs to be analyzed including other variables to predict entrepreneurial intent satisfactorily.
Keywords: entrepreneurship; creativity; self-efficacy; intention